American Society for Gastrointestinal Endoscopy–European Society of Gastrointestinal Endoscopy guideline on primary endoscopic bariatric and metabolic therapies for adults with obesity - Jirapinyo, Pichamol; Hadefi, Alia; Thompson, Christopher C.; Patai, Árpád V.; Pannala, Rahul; Goelder, Stefan K.; Kushnir, Vladimir; Barthet, Marc; Apovian, Caroline M.; Boskoski, Ivo; Chapman, Christopher G.; Davidson, Paul; Donatelli, Gianfranco; Kumbhari, Vivek; Hayee, Bu; Esker, Janelle; Hucl, Tomas; Pryor, Aurora D.; Maselli, Roberta; Schulman, Allison R.; Pattou, Francois; Zelber-Sagi, Shira; Bain, Paul A.; Durieux, Valérie; Triantafyllou, Konstantinos; Thosani, Nirav; Huberty, Vincent; Sullivan, Shelby (Endoscopy, 2024)
This joint ASGE-ESGE guideline provides an evidence-based summary and recommendations regarding the role of endoscopic bariatric and metabolic therapies (EBMTs) in the management of obesity. The document was developed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) framework. It evaluates the efficacy and safety of EBMT devices and procedures that currently have CE mark or FDA-clearance/approval, or that had been approved within five years of document development. The guideline suggests the use of EBMTs plus lifestyle modification in patients with a BMI of ≥30 kg/m2, or with a BMI of 27.0–29.9 kg/m2 with at least 1 obesity-related comorbidity. Furthermore, it suggests the utilization of intragastric balloons and devices for endoscopic gastric remodeling (EGR) in conjunction with lifestyle modification for this patient population.